Risk factor for gametocyte carriage and gametocytemia in Plasmodium vivax and Plasmodium falciparum - Minxi Li; Yang Bian; Shishao Ruan; Zifang Wu; Di Zhang; Tongyu Ma; Yaming Wu; Xiao Liu; Duo Wang; Jia Lin; Danni Pan; Wenyan Cui; et al. (Infectious Diseases of Poverty)
Abstract Background Understanding Plasmodium sexual differentiation is crucial for blocking transmission. This study identified risk factors for gametocyte carriage and gametocytemia in P. vivax and P. falciparum to inform malaria elimination strategies at the China-Myanmar border. Methods Gametocytes and asexual parasites were microscopically detected on thick smears collected from 2011 to 2020 in Laiza Township, Kachin State, Myanmar. Mono-/polyclonality were detected by genotyping at Pvmsp3α/β for P. vivax, and Pfmsp1/2 for P. falciparum. Kulldorff’s retrospective time scan statistics tested for likely clusters of gametocyte-positive cases over time. Chi-square or Fisher’s exact tests compared proportions of gametocyte-positive cases in categorical variables. Generalized linear models assessed risk factors (year, season, demographics, clinical/parasitological features) for gametocyte carriage (logistic regression for a binomial outcome) and gametocytemia (Gaussian regression for continuous outcome), respectively. Results During 2011–2020, 8240 patients had P. vivax infections, with 7249 testing positive for gametocytes. Among 510 P. falciparum cases, 56 tested positive for gametocytes. A significant cluster of P. vivax gametocyte carriage occurred from May 2015 to August 2017 (P = 0.001). For P. vivax, dry season, previous malaria history, fever, and parasite density were associated with gametocyte carriage. Gametocyte density increased with asexual parasite density (P < 0.001) but was lower during the rainy season and in those with a history of malaria infection (P < 0.001). Over time, gametocytes carriage proportion increased while density decreased (P < 0.001). For P. falciparum, younger age and previous malaria history were associated with gametocyte carriage, and density was higher in the dry season (P = 0.0115). Polyclonal P. vivax infections had higher gametocyte densities than monoclonal infections (P < 0.0001) and P. falciparum gametocyte density tended to increase with multiplicity of infection. Conclusions Younger age, prior malaria infection, travel, and polyclonal infections correlate with higher P. vivax gametocyte prevalence. Gametocyte carriage peakes during the dry season, highlighting the need for seasonal strategies to support malaria elimination. These findings enhance understanding of risk factors for the transmissible stage of the two main human Plasmodium species in the Greater Mekong Subregion border areas. Graphical Abstract